Reliability of accuracy and precision tests for elite para table tennis players - Galas, S.; Andrzejewski, M.; Pluta, B. (Adapted Physical Activity Quarterly, 2024)
The primary purpose of this study was to adapt selected accuracy and precision tests in table tennis to the specific skills of elite table tennis players with impairment. The study included a sample of 23 Para table tennis players with an average age of 31.8 ± 12.22 years (including 30.4% females) who belonged to the senior Polish Para table tennis team. A battery of six tests evaluating stroke accuracy and serve precision was assessed. The analysis of the reliability of these tests confirmed the legitimacy of using this battery of accuracy and precision tests to assess the skills of Para table tennis players in all three integrated sport classes: players in wheelchairs, in a standing position, and with intellectual impairment. Analysis of the data obtained from the tests could provide coaches with relevant information regarding elite Para table tennis players` level of performance and examine selected accuracy and precision elements of their individual technique.